COMPLEX CREDO - MODERN TECHNOLOGY FOR DEVELOPMENT PROJECTS OF TRANSPORT FACILITIES AND ROADS - Белятинський, А. О.; Утеченко, Т. О.; Резнік, О. М. (Science-based technologies, 2009)
It is considered opportunities of application of the newest technologies in designing highways and transport constructions. Advantages of this method and use of resulting development and materials other areas of the industry.